2020
DOI: 10.1186/s10397-020-01068-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hysterectomy versus total abdominal hysterectomy: a retrospective study at a tertiary hospital

Abstract: Objective: To compare laparoscopic hysterectomy (LH) with total abdominal hysterectomy (TAH) regarding different outcome measures at our tertiary hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
12
2
Order By: Relevance
“…Operative time was shorter in TAH than in LH (2.22 ± 0.93hours vs 2.43 ± 0.94 hours, respectively) but it was not statistically significant. [ 20 ] In our study, salpingectomy was performed at 57.8% in abdominal hysterectomy, 57% laparoscopic route, and 27% vaginal route ( p value 0.0001). A study by Natalie De Cure and Stephen showed VH had 15.9% salpingectomy, AH had 66.9%, and LH had 84.5% of salpingectomy.…”
Section: Discussionmentioning
confidence: 79%
“…Operative time was shorter in TAH than in LH (2.22 ± 0.93hours vs 2.43 ± 0.94 hours, respectively) but it was not statistically significant. [ 20 ] In our study, salpingectomy was performed at 57.8% in abdominal hysterectomy, 57% laparoscopic route, and 27% vaginal route ( p value 0.0001). A study by Natalie De Cure and Stephen showed VH had 15.9% salpingectomy, AH had 66.9%, and LH had 84.5% of salpingectomy.…”
Section: Discussionmentioning
confidence: 79%
“…13 The same has been found in the study by Aboulfotouh et al, where the size of the uterus was significantly smaller in the laparoscopic group compared to the abdominal group. 14 The probable reason could be the selection criteria by the gynecologists since many prefer performing laparoscopic hysterectomy on small uteri.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because women come from far-off rural villages and they did not want to get discharged early. Other studies[ 8 11 16 ] also mentioned the duration of hospital stay of about 3–7 days.…”
Section: Discussionmentioning
confidence: 99%